(untitled) - Tewoldemedhin, Yared Tesfai

Characterisation of Rhizoctonia in cropping systems in the Western Cape Province (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScAgric (Plant Pathology))--University of Stellenbosch, 2005.